Cardol: Cashew nut shell liquid (CNSL) - derived starting material for the preparation of partially bio-based epoxy resins. (5th March 2022) - Makwana, Ketan; Ichake, Amol B.; Valodkar, Vinayak; Padmanaban, G.; Badiger, Manohar V.; Wadgaonkar, Prakash P.
Graphical abstract: Highlights: Cardol was exploited as a starting material for synthesis of partially bio-based epoxy resins. Cardol-based epoxy resin was a low viscous liquid offering ease of processing. The modulation of Tg values of epoxy thermosets was demonstrated. Abstract: Cardol is one of the interesting constituents of cashew nut shell liquid (CNSL) - a by-product of cashew processing industry- and it amounts to 15–20% by weight in natural CNSL. Chemically, cardol is a 15-carbon chain-substituted resorcinol wherein the side chain predominately contains mixture of one, two and three double bonds. Cardol on reaction with epichlorohydrin in the presence of sodium hydroxide afforded diglycidyl ether of cardol (DGEC). DGEC is a viscous free-flowing liquid (bulk viscosity 70 cP at 25 °C) and thus offers advantages in terms of ease of processing. DGEC and various compositions of DGEC with commercially available diglycidyl ether of bisphenol A (DGEBA) were cured with two amine hardeners, namely, isophorone diamine (IPDA) and diethylene triamine (DETA). The effects of different ratios of amine/epoxy (nah /ne ) on cure characteristics were studied. The epoxy thermosets were characterized by DSC, TGA, DMA and tensile testing. DSC analysis showed glass transition temperature ( T g ) values in the range 63–155 °C for IPDA-cured thermosets, while DETA-cured thermosets exhibited T g values in the range 45–145 °C. T d5% values, determined by TG analysis of epoxy thermosets, were in the range 347–359 °C indicating their reasonably good thermal stability. Dynamic mechanical analysis showed storage modulus (E') in the range 0.75–2.54 GPa and 0.51–2.24 GPa for IPDA-cured and DETA-cured thermosets, respectively. The E' value of epoxy thermosets was found to decrease with increase in molar proportion of DGEC in the formulations with DGEBA while elongation at break was found to increase from 3.1% to 9.7% and 2.8% to 5.1% for IPDA- and DETA-cured systems, respectively. SEM images of cryogenically fractured surfaces of cured thermosets based on studied compositions of DGEBA and DGEC did not indicate any phase separation implying homogeneous mixing of both the epoxy resins.